2014
DOI: 10.24084/repq12.455
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of PV generation based on spherical irradiation measurements

Abstract: Abstract. In this paper spherical irradiation measurements are exploited and compared to power output in order to assess PV system generation potential. Not the spherical irradiation as a sum is measured, but irradiation referred to a specific solid angle. This approach enhances generation forecasting for predefined panel orientations within urban areas. In urbanised regions sophisticated shadowing and reflexion patterns result generally in complicated generation predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Such a measuring device can consist of one or more measuring cells that are locally installed close to the PV system. Evidence that a PV system can be simulated accurately by a simple measuring device is shown [19]. It was demonstrated that a PV system with various geographical orientations of panels can be mapped by a few cells with acceptable error.…”
Section: Modeling Of Feature-dependent Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a measuring device can consist of one or more measuring cells that are locally installed close to the PV system. Evidence that a PV system can be simulated accurately by a simple measuring device is shown [19]. It was demonstrated that a PV system with various geographical orientations of panels can be mapped by a few cells with acceptable error.…”
Section: Modeling Of Feature-dependent Generationmentioning
confidence: 99%
“…The measuring instrument consists of 33 measuring cells arranged on a spherical surface. As shown in [19], such a measuring instrument can be used to perform an almost exact reproduction of each photovoltaic system in the immediate vicinity of the measuring device. From the measured values, an average curve for each cell was created separately for the period of summer.…”
Section: Feature-dependent Generationmentioning
confidence: 99%